The Tatra Mts – rocks, landforms, weathering and soils - Drewnik, Marek; Felisiak, Ireneusz; Jerzykowska, Irena; Magiera, Janusz (Geotourism/Geoturystyka, 2018)
The trip gives insight into geology and landforms as well as into past and present dynamic geological, geomorphologic and soil-forming processes in the central part of Polish Tatra Mts. The area is easily accessible from Zakopane. However not the highest and not the most impressive of all parts of the mountains it offers a concise review of all sites crucial for understanding the geologic history of the Tatras and their forefield. Crystalline core has not only been covered by overthrusted sedimentary rocks but also forms tectonically displaced bodies like crystalline islands over the sediments. Post-orogenic erosion strongly differentiated the mountains landscape. High valleys shaped in resistant granitoids of the High Tatras were much better reservoirs of snow and ice during the Pleistocene then the West Tatras valleys deeply cut into softer sediments and metamorphic rocks. Therefore, the High Tatric glaciers were longer and thicker than the West Tatric ones. Post-glacial weathering, mass movements and accumulation of organic matter resulted finally in formation of rich variety of specific mountain soils. // Trasa wycieczki prowadzi przez środkową część Tatr Polskich: Dolinę Bystrej, Kasprowy Wierch, przełęcz Karb i Dolinę Suchej Wody (Fig. 1). Różnice między dwiema głównymi częściami tych gór: Tatrami Zachodnimi i Wysokimi są stamtąd wyjątkowo dobrze widoczne. Teren ten jest ponadto przedmiotem intensywnych badań od przynajmniej 200 lat, a najnowsze doniesienia pojawiają się co roku. Stamtąd pochodzą liczne datowania moren, wreszcie, to w Dolinie Suchej Wody L. Zejszner pierwszy rozpoznał w 1849 r. ślady zlodowacenia. Przemierzając Tatry podczas planowanej wycieczki będzie można zaobserwować tak wyraźnie widoczne w górach efekty działania procesów prowadzących do niszczenia gór, bardziej szczegółowo przyjrzymy się przejawom wietrzenia. Wietrzenie jest bardzo ważnym procesem warunkującym powstawanie gleb a co za tym idzie wpływającym na rozwój roślin i zwierząt czyli na środowisko życia człowieka.